2007
DOI: 10.1002/cphc.200700091
|View full text |Cite
|
Sign up to set email alerts
|

Single Dibenzoterrylene Molecules in an Anthracene Crystal: Spectroscopy and Photophysics

Abstract: We study single dibenzoterrylene molecules in an anthracene single crystal at 1.4 K in two insertion sites at 785.1 and 794.3 nm. The single-molecule zero-phonon lines are narrow (about 30 MHz), intense (the detected fluorescence rates at saturation reach 100,000 counts s(-1)), and very photostable. The intersystem-crossing yield is extremely low (10(-7) or lower). All of these features are hallmarks of an excellent system for high-resolution spectroscopy and nanoscale probing at cryogenic temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
116
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(131 citation statements)
references
References 37 publications
(47 reference statements)
13
116
1
1
Order By: Relevance
“…dE rel is the energy of a given isomer in the ground electronic state with respect to the energy of the most stable isomer. [9], and 765.5 and 794.2 nm for the two DBT sites in anthracene crystals [11]. The small differences between transition energies DE of different isomers and broad fluorescence bands at 270 K [21] seem to exclude conformation changes of DBT as the possible origin of their photo-bleaching.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…dE rel is the energy of a given isomer in the ground electronic state with respect to the energy of the most stable isomer. [9], and 765.5 and 794.2 nm for the two DBT sites in anthracene crystals [11]. The small differences between transition energies DE of different isomers and broad fluorescence bands at 270 K [21] seem to exclude conformation changes of DBT as the possible origin of their photo-bleaching.…”
Section: Resultsmentioning
confidence: 98%
“…DBT molecules were already successfully studied by the single molecule spectroscopic technique in naphthalene [8,9] and anthracene [10][11][12] crystals. It was shown that the lowest excited S 1 state of this dye is red shifted in comparison with Tr.…”
Section: Introductionmentioning
confidence: 99%
“…9 When cooled to low temperatures, these molecules emit with high (34%) efficiency on the zero-phonon line, and with lifetime-limited linewidth. 10,11 The molecules are exceptionally photostable, even at room temperature, and their optical dipole moments align naturally with one of the axes of the anthracene crystal. 12 Toninelli et al have shown coupling of DBT to an optical cavity 13 and Hwang and Hinds have a) kyle.major11@imperial.ac.uk b) ed.hinds@imperial.ac.uk discussed the exchange of radiation between the molecular dipole and other optical structures.…”
Section: Introductionmentioning
confidence: 99%
“…At cryogenic temperature and in suitable rigid matrixes, the absorption spectrum of a molecule presents an extremely narrow electronic transition that occurs without any creation or annihilation of phonons, and is therefore called the zerophonon line (ZPL). Its linewidth is chiefly determined by the lifetime of the excited state and lies in the range of 10-50 MHz for many well-studied host-guest systems [13][14][15][16][17][18][19]. Because of its sharpness, the ZPL is extremely sensitive to the molecule's local environment.…”
mentioning
confidence: 99%
“…We can thus use a single molecule to detect the local vibrations by monitoring the instantaneous frequency of its ZPL. In the present work, we chose single dibenzoterrylene (DBT) molecules embedded in an anthracene (Ac) crystal because of the stability of their ZPL, of their lifetime-limited linewidth and of their convenient wavelength [16].…”
mentioning
confidence: 99%